What's new Scooby-Doo? [videorecording (DVD)] Complete 2nd season - Kasem, Casey; Welker, Frank; Cohn, Mindy, 1966-; DeLisle, Grey (Warner Home Video, 2007)
There's no business like ghost business, and when you join Mystery Inc. you get to travel. On an endless summer vacation, visiting six different countries from around the goblin globe, uncover all the ghouls, ghosts, mummies, vampires, and more.